El garage invisible (2005)
El proyecto del garage subterráneo contempla la preservación de la plaza y su uso público. Por <MMBB>
Keywords: BUCCI, ANGELO; MELLO, FERNANDO FRANCO DE; MOREIRA, MARTA; BRAGA, MILTON; SAN PABLO; BRASIL; ESTACIONAMIENTOS SUBTERRANEOS; PLAZAS; CONSTRUCCION SUBTERRANEA